«ҲӘЎЖАР» ҚОСЫҒЫНЫҢ ПАЙДА БОЛЫЎ ДӘРЕКЛЕРИ - Палымбетов, К.С. (SCIENCE and SOCIETY, 2024)
The article highlights the "hәujar" and "jor-jor" songs associated with the wedding ceremony among the Karakalpak people. The origins of the hәujar and jor-jor songs performed at Karakalpak weddings are analyzed, and evidence is presented to demonstrate that these songs have their roots in ancient times.